WORK SATISFACTION AMONG EMPLOYEES AT VIRASAT-E-KHALSA: ANANDPUR SAHIB - Garg, Ankit (International Journal of Research -GRANTHAALAYAH, 2016)
Work satisfaction is a general attitude of employees towards one’s job. The present study is undertaken to assess the work satisfaction among employees at Virasat-e-Khalsa through percentage and graphic analysis. The sample size of 30 respondents was selected through convenience sampling. It was found that overall satisfaction was moderate, however, salary and job security are a major concern for the youth working there. It was suggested that job satisfaction may be improve by assuring regular appointments and increments in remuneration.